M-learning application for un-typed lambda calculus - Meza, Daniel (2014)
The main objective of this research is to generate a mobile aiding tool that can help students with different learning styles and experiences to gain more knowledge in the lectures by participating in different activities that will teach them how to properly learn from the lectures and hopefully enjoy while doing it by using games and different strategies that aim for different types of learners. Based on own experiences on different modules at the University of Nottingham, a lack of different aiding tools was noticed during lectures which turns into students losing interest and lagging behind trying to absorb too much information and too many new terms. With an increase demand of mobile technologies and the benefits of m-learning techniques being used to aid different fields of knowledge; an opportunity to make use of these powerful tools and take advantage of the ubiquitous nature of mobile devices will allow and engage students to learn, evaluate, judge, criticize all the new knowledge shown to then in the lectures in an stress free environment without repercussions and at their own pace. The application was created for iPhone devices and makes use of gaming frameworks to help show important information and to make it more interactive to students. It also introduces the implementation of 5 different learning techniques into the app that allows different types of learners to get familiarized with the new terms of Lambda Calculus by showing the contents of the lectures in an innovative way. The app improves learning by making use of a lambda calculator that allows students to check the result of operations step by step, a true and false type of game that let users test their knowledge without repercussions, and a tool containing all the main definitions of the lecture in just one place so it can be easy to find and refer. The application proved itself to be useful for students with little or no knowledge of Lambda Calculus and introduced them to the main topics of functional programming in an innovative way and students who had some knowledge of the subject noted the advantages and possible uses of the application if it would have existed at the moment they were studying Lambda Calculus. Overall results showed that the application is a very resourceful tool that works well, give students a sense of gaining knowledge in an interactive way by having fun playing games and changes the traditional way Lambda Calculus is being introduced by making it more accessible, understandable and interesting.